Association between Genetic Variants in DUSP15, CNTNAP2, and PCDHA Genes and Risk of Childhood Autism Spectrum Disorder. (29th June 2021) - Fang, Fang; Ge, Minxia; Liu, Jun; Zhang, Zengyu; Yu, Hong; Zhu, Shuilong; Xu, Liwei; Shao, Lina
Abstract : Objective . Genetic factors play an important role in the development of autism spectrum disorder (ASD). This case-control study was to determine the association between childhood ASD and single nucleotide polymorphisms (SNPs) rs3746599 in the DUSP15 gene, rs7794745 in the CNTNAP2 gene, and rs251379 in the PCDHA gene in a Chinese Han population. Methods . Genotypes of SNPs were examined in DNA extracted from blood cells from 201 children with ASD and 200 healthy controls. The Children Autism Rating Scale (CARS) was applied to evaluate the severity of the disease and language impairment. The relationship between SNPs and the risk of ASD or the severity of the disease was determined by logistic regression and one-way ANOVA. Results . The genotype G/G of rs3746599 in the DUSP15 gene was significantly associated with a decreased risk of ASD (odds ratio OR = 0.65, 95% confidence interval (CI): 0.42-0.99, P = 0.0449 ). The T allele of rs7794745 in the CNTNAP2 gene was associated with an increased risk of ASD (OR = 1.34, 95% CI: 1.01-1.77, P = 0.0435 ). The SNP rs251379 was not associated with ASD. Though none of the SNPs examined were associated with ASD severity, rs7794745 was associated with severity of language impairment. Conclusions . Our findings suggest that both rs3746599 in the DUSP15 gene and rs7794745 in the CNTNAP2 gene are associated with risk of childhood ASD, and rs7794745 is also related to the severity of language impairment in autistic children from a Chinese Han population.